A survey of the literary achievements in Venda : a descriptive study from the earliest beginnings up to 1970 - Mathivha, Matshaya Edward Razwimisani (University of Limpopo, 1972)
Refer to the document
Thesis (Ph.D.(African Languages)) -- University of the North, 1972
Keywords: Venda literature; Venda language; Venda language -- Texts; Venda literature -- Criticism, interpretation, etc.